2019
DOI: 10.1080/14693062.2019.1617667
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for hydropower-based nationally determined contributions: a case study for Ecuador

Abstract: Hydropower is the dominant renewable energy source to date, providing over two-thirds of all renewable electricity globally. For countries with significant hydropower potential, the technology is expected to play a major role in the energy transition needed to meet nationally determined contributions (NDCs) for greenhouse gas (GHG) emission reductions as laid out in the Paris Agreement. For the Republic of Ecuador, large hydropower is currently considered as the main means for attaining energy security, reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Moreover, climate-induced changes in agricultural practices are anticipated across tropical latitudes, spurred by rising temperatures and alterations in rainfall patterns. Particularly in the highlands of Ecuador, a projected decrease in precipitation could severely impact water resources, posing challenges to urban water supply and hydroelectric generation (Buytaert et al, 2009;Lawrence and Vandecar, 2015;Ovalle-Rivera et al, 2015;Carvajal and Li, 2019). Our study aligns with these observations, revealing significant vulnerabilities in specific ecosystems under the RCP 8.5 scenario.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, climate-induced changes in agricultural practices are anticipated across tropical latitudes, spurred by rising temperatures and alterations in rainfall patterns. Particularly in the highlands of Ecuador, a projected decrease in precipitation could severely impact water resources, posing challenges to urban water supply and hydroelectric generation (Buytaert et al, 2009;Lawrence and Vandecar, 2015;Ovalle-Rivera et al, 2015;Carvajal and Li, 2019). Our study aligns with these observations, revealing significant vulnerabilities in specific ecosystems under the RCP 8.5 scenario.…”
Section: Discussionsupporting
confidence: 85%
“…This study only focuses on hydropower potential, while including the other renewable energy technologies (e.g., wind and solar) would not virtually affect the estimation of the hydropower capacity, as it does not compete for common resources and can be used for peak time hours (Anderson et al, 2006). It is indeed a more flexible and stable technology than other renewable energy technologies (Carvajal & Li, 2019). A consideration of the other technologies and renewable resource mix would benefit the whole energy system in the further work (Mesfun et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Based on Carvajal's (2019) analysis of Ecuador's energy grid, it is clear that hydropower is affected by climate change and, thus, a partial equilibrium model is needed for the energy system. It was found that the proportion of Ecuador's total electricity produced by hydropower could vary significantly by 2050 (between 53% and 81%) and this could be attributed to a dry climate scenario, as well as social resistance that could limit the implementation of large-scale hydroelectric projects in the country [14].…”
Section: Introductionmentioning
confidence: 99%